-2a+3=-12

Simple and best practice solution for -2a+3=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+3=-12 equation:


Simplifying
-2a + 3 = -12

Reorder the terms:
3 + -2a = -12

Solving
3 + -2a = -12

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2a = -12 + -3

Combine like terms: 3 + -3 = 0
0 + -2a = -12 + -3
-2a = -12 + -3

Combine like terms: -12 + -3 = -15
-2a = -15

Divide each side by '-2'.
a = 7.5

Simplifying
a = 7.5

See similar equations:

| -5(x+3)+5(x-2)=-x+10 | | 3(y-9)+5=35 | | 1.2x-3.6=2.4-0.3x | | 1-3mx=9x-8 | | -3n=-27n-63 | | 3x+2(5x+2)=147 | | -3(-4x-8)=60 | | 2mx+1=4x-3 | | -3/8+k=-7/18 | | 4h^2+9h-28=0 | | -7(-3x-8)=140 | | -3(-6-2x)=-24 | | 28*1-18*1+30=40 | | f(-3)=2/3(-3)+3 | | 2x+4+3y=22 | | 10x+5=3x+7 | | (4x-12)= | | -6+x+x=6 | | -10x+15=-35 | | 5(2x+1)+3(x-7)=-3 | | 6=2x-x+7 | | f(9)=2/3(9)+3 | | X-2*x-32=0 | | 18=2x+7x+9 | | 5.75x-5+x=5(5.25) | | 5(x+3)=3-1(2x) | | -6x+1-3x=73 | | -2.5y+6.7=-1.3 | | 103+10a=113 | | (x+15)= | | X=80+(-4.5y) | | 7=-2x+x-3 |

Equations solver categories